2023
DOI: 10.1021/acs.jpcb.2c06872
|View full text |Cite
|
Sign up to set email alerts
|

Benchmarking Thiolate-Driven Photoswitching of Cyanine Dyes

Abstract: Carbocyanines are among the best performing dyes in single-molecule localization microscopy (SMLM), but their performance critically relies on optimized photoswitching buffers. Here, we study the versatile role of thiols in cyanine photoswitching at varying intensities generated in a single acquisition by a microelectro­mechanical systems (MEMS) mirror placed in the excitation path. The key metrics we have analyzed as a function of the thiolate concentration are photon budget, on-state and off-state lifetimes … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

2
3

Authors

Journals

citations
Cited by 5 publications
(5 citation statements)
references
References 64 publications
(193 reference statements)
0
5
0
Order By: Relevance
“…The AF488 fluorophore excited state can be quenched via FRET with AF647 in addition to a distance dependent quenching by the gold surface, so a correlation to coverage is limited to cases where the FRET efficiency is low. On the other hand, AF647 intensities are only quenched by the gold surface and should in principle be directly correlated to coverage, but study of the photophysics of AF647 has shown the formation of dark states , which limits its use as a measure of coverage. This is clear when analyzing the AF647 ssDNA SAM image which shows a darker than usual central portion of the bead where the 111 facet has a significantly lower intensity when compared to the 111 facet on the side of the bead.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…The AF488 fluorophore excited state can be quenched via FRET with AF647 in addition to a distance dependent quenching by the gold surface, so a correlation to coverage is limited to cases where the FRET efficiency is low. On the other hand, AF647 intensities are only quenched by the gold surface and should in principle be directly correlated to coverage, but study of the photophysics of AF647 has shown the formation of dark states , which limits its use as a measure of coverage. This is clear when analyzing the AF647 ssDNA SAM image which shows a darker than usual central portion of the bead where the 111 facet has a significantly lower intensity when compared to the 111 facet on the side of the bead.…”
Section: Resultsmentioning
confidence: 99%
“…It appears that FRET intensities do not suffer from the decrease in AF647 fluorescence due to this dark state. This can be explained recognizing that for FRET imaging, a 480 nm excitation is used which has been reported to facilitate the depopulation of the AF647 dark state back into its ground state. , The same effect is apparently occurring in these FRET images. Separate measurements of a 100% AF488 modified DNA were performed and showed a very similar pattern to the AF488 fluorescence images in the mixed composition layers suggesting that the FRET quenching of AF488 intensity may not be as significant (see Figure S10).…”
Section: Resultsmentioning
confidence: 99%
“…The first methods for achieving SMLM were shown with photo-activated localisation microscopy (PALM), where the specimen was imaged and subsequently bleached through depth [ 50 ], and stochastic orientation reconstruction microscopy (STORM), which used photo-switchable fluorophores to image single molecules over several thousand image frames [ 51 ]. Subsequently, the use of conventional cyanine dyes with specialised buffer solutions became increasingly popular [ 52 ], allowing for direct STORM (dSTORM), the direct nature coming from the fact that fluorescent antibody pairs are not required [ 53 , 54 ]. More recently, fluorescent transiently-binding single DNA strands have re-emerged as a versatile tool, allowing for improved single molecule localisation with the development of point accumulation in nanoscale topography (DNA-PAINT) [ 55 ].…”
Section: Super-resolution Microscopy – a New Era Of Microscopymentioning
confidence: 99%
“…However, these studies focused only on thiol-induced photoswitching, particularly during the switchingoff step. [20][21][22][23][24] For example, a reversible transition occurs between the fluorescent and dark transient states, in which the formation of a nonemissive cyanine dye-thiolate (CyÀ SR) adduct is mainly responsible for the switching-off step. However, the detailed mechanism by which the fluorescent state is recovered remains unclear.…”
Section: Introductionmentioning
confidence: 99%
“…To reconcile the seemingly divergent results reported by several groups, efforts have recently been made to unify the different mechanisms for thiol‐induced photoswitching of cyanine dyes, which are the most utilized dyes for SMLM. However, these studies focused only on thiol‐induced photoswitching, particularly during the switching‐off step [20–24] . For example, a reversible transition occurs between the fluorescent and dark transient states, in which the formation of a nonemissive cyanine dye‐thiolate (Cy−SR) adduct is mainly responsible for the switching‐off step.…”
Section: Introductionmentioning
confidence: 99%